2014
DOI: 10.1637/10626-080513-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Characterization of Rotavirus A in Broilers, Layers, and Broiler Breeders from Brazilian Poultry Farms

Abstract: Rotaviruses are a major cause of diarrhea in humans and animals, including several mammalian and avian species. Using different PCR protocols, we report the occurrence of rotavirus A in 21 (53.84%; 21/39) from 39 fecal pool samples of broilers, layers, and broiler breeders from Brazilian avian farms. We typed the G5, G8, G11, G19, and P[31] genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
2
10
0
5
Order By: Relevance
“…Highest prevalence has been observed (40%) in 12-day-old birds while the lowest was observed in birds aging 22 days (6%) (Ahmed & Ahmed 2006;Karim et al 2007). A recent study in Brazil revealed 53.8% prevalence of rotavirus from broilers, layers and broiler breeders (Beserra et al 2014). In countries like Bangladesh, RV disease is reported as 0.9% of diarrheic broilers (Ahmed 2013).…”
Section: Epidemiologymentioning
confidence: 99%
“…Highest prevalence has been observed (40%) in 12-day-old birds while the lowest was observed in birds aging 22 days (6%) (Ahmed & Ahmed 2006;Karim et al 2007). A recent study in Brazil revealed 53.8% prevalence of rotavirus from broilers, layers and broiler breeders (Beserra et al 2014). In countries like Bangladesh, RV disease is reported as 0.9% of diarrheic broilers (Ahmed 2013).…”
Section: Epidemiologymentioning
confidence: 99%
“…Dandar et al (2013) characterized divergent avian reovirus strain from a broiler chicken with central nervous system disease. For the first time, Beserra et al (2014) reported the occurrence of rotavirus group F in broiler from Brazil. Gyuranecz et al (2013) established worldwide phylogenetic relationship of avian poxviruses and provided novel insights into the complex relationship between avian poxviruses and their hosts.…”
Section: Classical Methods For Study Of Virus Diversitymentioning
confidence: 99%
“…No Brasil não existem estudos de genoma completo de AvRV e os dados acerca da diversidade genética dos mesmos é limitada, ficando restrito à caracterização dos genotipos G, P e E (ASANO et al, 2011;SILVA et al, 2011;SILVA et al, 2012;METTIFOGO et al, 2014;BESERRA et al, 2014a).…”
Section: Estrutura E Classificaçãounclassified
“…Foram descritos até o momento, sete genotipos G -G1, G5, G6, G8, G10, G11 e G19 -três genotipos P -P (ASANO et al, 2011;SILVA et al, 2012;BESERRA et al, 2014a). Está descrito ainda o genotipo E10, detectado em amostras de frango de corte dos estados do Pará e São Paulo (SILVA et al, 2011;METTIFOGO et al, 2014).…”
Section: Estrutura E Classificaçãounclassified
See 1 more Smart Citation